Plan de negocios para la producción y exportación de jabón de arroz a Berlín – Alemania - González Romero, Estefanía Gissela (2018)
The following project aims to determine the feasibility of creating a company dedicated to the production and export of a soap based on brown rice and other natural ingredients; such as, coconut oil and aloe Vera to Berlin in Germany. To achieve the objective, inquiries were made about the industry environment, where the product is offered, an analysis of potential customers through quantitative and qualitative research, the business opportunity was determined, focused on its differentiating factor; in this case, a competitive advantage; the marketing plan necessary to establish the characteristics of the product, the price strategy, the promotion strategies and the place where the product is available, as well as an operations plan that helps to use the resources of the company efficiently. Finally, a financial analysis is prepared in order to determine if the project is viable and profitable. The idea is to offer a product that highlights the benefits of the agricultural country inputs in an international market. The choice of the country was made taking into account the advantages and preferential rates that are available thanks to the Multi-Party Trade Agreement between Ecuador and the European Union. Through this project, it is possible to observe that Ecuador is capable of create industrialized products and export them, so encouraging more companies to contribute to the growth and development of the country. In conclusion, the financial evaluation was carried out over a period of 5 years, which showed a positive return and investment criteria that evidence that the project is viable, since a NPV of $ 45,829.11 is recorded, the IR of 2 , 09% and an IRR of 47.82%. Additionally, the net profit margin in the fifth year reflects a rate of 5.86%, which also proves the feasibility and success of the business.